2014
DOI: 10.20883/medical.e74
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ awareness of radiation exposure related to radiological imaging procedures

Abstract: Introduction. Current advancements in fields of medical sciences resulted in an increase of imaging examinations with a use of ionising radiation. Such increase leads to justified concerns about its possible consequences.Aim. Assessment of awareness and level of knowledge of medicine students in terms of ionising radiationMaterial and methods. Statistical analysis of 207 surveys of medical students from University of Medical Sciences in Poznan (UMP), Poland with use of Statistica softwareResults. There was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Exposure to ionizing radiation without appropriate justification is discouraged because of deterministic and stochastic effect [10]. It was reported that knowledge of clinicians on ionizing radiation is inadequate [11]. The present study aims at evaluating the knowledge of non-radiology physicians in our own locality, in order to review local protocols on justification of investigations involving ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ionizing radiation without appropriate justification is discouraged because of deterministic and stochastic effect [10]. It was reported that knowledge of clinicians on ionizing radiation is inadequate [11]. The present study aims at evaluating the knowledge of non-radiology physicians in our own locality, in order to review local protocols on justification of investigations involving ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%